Clinical characteristics and prognostic value of the KRAS mutation in Chinese colorectal cancer patients. Issue 2 (June 2021) - Yuan, Ye; Liu, Yingting; Wu, Ye; Zhang, Junling; Shen, Chunti; Zhang, Feng; Wu, Changping; Hu, Wenwei
Background: The KRAS mutations are high-frequency somatic mutations found in colorectal cancer patients from Western and Asian countries however, with the exception of exon 2 of KRAS, other prevalence and prognostic values have not been adequately assessed in Asian patients. The aim of this study was to determine the mutation frequencies of whole exon mutations of KRAS in Chinese colorectal cancer patients and to investigate their impact on prognosis. Methods: A total of 7189 tumor tissue samples (iCohort) were subjected to next-generation sequencing for detection of KRAS mutations. All pathologic or likely pathologic mutations of KRAS were considered. In addition, clinical features and prognostic dates were collected from 145 patients at The Third Affiliated Hospital of Soochow University, China (sCohort) and used droplet digital™ polymerase chain reaction to detect KRAS mutations. Results: In the iCohort, 2706 patients (37.6%) were confirmed harboring KRAS mutations. The most frequent of these mutations were G12D (32.19%), G12V (17.96%), and G13D (17.59%). In the sCohort, 51 colorectal cancer patients (35.17%) had KRAS mutations, among which KRAS G12D (64.71%), G13D (29.41%), and G14D (3.92%) were high-frequency. The KRAS mutations were associated with shorter median overall survival than wild-type tumors (69 vs. 55 months; HR 1.80; 95% Cl 1.22, 2.64; P =0.0003). In the Cox multivariate analysis, age (HR 1.562; 95% Cl 1.10, 2.22; P =0.013), tumor differentiation (HR 0.417; 95% Cl 0.19, 0.90; P =0.026), and KRAS mutation (HR 1.897; 95% Cl 0.19, 0.90; P =0.001) remained independent predictors of shorter overall survival. Among the common KRAS mutations, G12D was significantly associated with shorter overall survival (HR 2.17; 95% Cl 1.31, 3.58; P < 0.0001) compared with KRAS wild-type patients. Conclusions: Our findings indicate that KRAS genes are frequently mutated, and over 30% harbored the KRAS G12D mutation subtype. We found that the KRAS G12D mutation is associated with inferior survival and is a biomarker of poor prognosis in Chinese patients. Our data emphasize the importance of molecular features in colorectal cancer patients, which could potentially be improved by G12D -specific related inhibitors.